2018
DOI: 10.1039/c8tc04799e
|View full text |Cite
|
Sign up to set email alerts
|

Growth and in-plane undulations of GaAs/Ge superlattices on [001]-oriented Ge and GaAs substrates: formation of regular 3D island-in-network nanostructures

Abstract: Coherently strained pseudo-superlattices (PSLs) of 20-period GaAs/Ge have been epitaxially grown on [001]-oriented Ge and GaAs substrates by metalorganic chemical vapor deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…[8,26] The underlying substrate induces strain in the film, which in case of Ge on GaAs is compressive. [19,43] This strain tends to be compensated by Ge segregation [19] and enlargement of Ge lattice in the growth direction. [43] Strong interaction of Ge atom with GaAs, along with Ge segregation and annealing induced atomic diffusion, gives rise to observed polytype of GaAsGe NIs (Figure 1, S1, and Figure 4) with additional presence of oxygen as mentioned earlier.…”
Section: Morphological Evolution Of Nanostructuresmentioning
confidence: 99%
See 4 more Smart Citations
“…[8,26] The underlying substrate induces strain in the film, which in case of Ge on GaAs is compressive. [19,43] This strain tends to be compensated by Ge segregation [19] and enlargement of Ge lattice in the growth direction. [43] Strong interaction of Ge atom with GaAs, along with Ge segregation and annealing induced atomic diffusion, gives rise to observed polytype of GaAsGe NIs (Figure 1, S1, and Figure 4) with additional presence of oxygen as mentioned earlier.…”
Section: Morphological Evolution Of Nanostructuresmentioning
confidence: 99%
“…Such alloying of GaAs and Ge may result in lattice constant larger than that calculated by Vegard's Law. [19,38] A detailed study of Ge interaction and its diffusion in GaAs atomic planes can be found in a paper by Sozen et al. [20] Furthermore, there is evidence in the literature that Ga vacancies are the most probable source of increased diffusion of Ge [27,42] when grown over GaAs, [22] and that the phenomena is governed by annealing parameters.…”
Section: Morphological Evolution Of Nanostructuresmentioning
confidence: 99%
See 3 more Smart Citations